Analysis of Protection System on Three-phase Induction Motor PT South Pacific Viscose - Toriq Hidayatul Madinah; Dian Budi Santoso (Jurnal Ilmiah Wahana Pendidikan, 2023)
This paper describes the three-phase induction motor protection system used in PT South Pacific Viscose. The induction motor studied is a motor with a power of 90 kW. The nominal current obtained from the calculation is 151.934 A. Protection system in the form of MCCB and TOR. From the results of the calculation of the MCCB rating that must be used 379.835 A and the TOR rating of 189.917 A, while the installed MCCB is 400 A and TOR 200 A. By comparing the results of calculation observations with the field, it can be concluded that the use of the protection system is appropriate.